2018
DOI: 10.3390/met8050296
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Fatigue Damage Accumulation of Ti–6Al–4V under Constant and Sequenced Variable Loading Conditions

Abstract: Abstract:This study aims to investigate the effect of loading factors on damage accumulation under variable amplitude vibration (VAV). Vibration fatigue experiments are conducted under both constant amplitude vibration (CAV) and VAV loading cases. The effects of loading sequence, loading amplitude, stress difference, and cyclic ratio on damage accumulation are analyzed. It is found the damage accumulation rate is strongly affected by the loading sequence: the fatigue lives can be ranked in descending order as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…After an extensive literature search, it has shown that the random vibration signals have crucial effects on fatigue life. Lin et al [18] performed a vibration fatigue analysis on engine structures using random loadings to study the effects of damage summation rule under different load sequences. In vibration fatigue analysis, when an event of the loading signals matched with the structural frequencies, the vibrations are amplified [19].…”
Section: Introductionmentioning
confidence: 99%
“…After an extensive literature search, it has shown that the random vibration signals have crucial effects on fatigue life. Lin et al [18] performed a vibration fatigue analysis on engine structures using random loadings to study the effects of damage summation rule under different load sequences. In vibration fatigue analysis, when an event of the loading signals matched with the structural frequencies, the vibrations are amplified [19].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al 25 investigated the fatigue life of Ti‐6Al‐4V titanium alloy treated by vibratory stress relief. Lin et al 26 have studied the effect of loading factors on damage accumulation under variable amplitude vibration.…”
Section: Methodsmentioning
confidence: 99%
“…For the fatigue strength and stress cycle number (S-N) curves of the three materials mentioned, the literature on fatigue strength of these materials was found; titanium alloy Ti-6Al-4V was found in references [15]- [18], PEEK material in [19] and stainless steel material AISI 304L [20].…”
Section: D Finite Element Modelmentioning
confidence: 99%